2003
DOI: 10.1139/y03-051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid-induced esophagitis on esophageal smooth muscle

Abstract: Acid-induced esophagitis is associated with sustained longitudinal smooth muscle (LSM) contraction and consequent esophageal shortening. In addition, LSM strips from opossums with esophagitis are hyper-responsive, while the circular smooth muscle (CSM) contractility is impaired. To determine the origin of these changes, studies were performed on esophageal smooth muscle cells isolated from opossum esophagi perfused intraluminally on 3 consecutive days with either saline (control; n = 8) or HCl (n = 9). CSM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…The protocol used for isolation of CSMC was similar to that previously described [39]. Briefly, the mid-descending colon was removed and placed in fresh Krebs' solution (in mM: NaHCO 3 25; NaCl 118; KCl 4.7; NaH 2 PO 4 1; MgSO 4 1.2; glucose 11; CaCl 2 2.5; bubbled with 95%O 2 /5%CO 2 ).…”
Section: Isolation Of Circular Smooth Muscle Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol used for isolation of CSMC was similar to that previously described [39]. Briefly, the mid-descending colon was removed and placed in fresh Krebs' solution (in mM: NaHCO 3 25; NaCl 118; KCl 4.7; NaH 2 PO 4 1; MgSO 4 1.2; glucose 11; CaCl 2 2.5; bubbled with 95%O 2 /5%CO 2 ).…”
Section: Isolation Of Circular Smooth Muscle Cellsmentioning
confidence: 99%
“…To address these questions, we have modified a recently developed cell isolation technique [39] to obtain a high yield of long, viable SMC that likely represents the in vivo status of the cell, and can thus optimally identify alterations in cellular contractility. We applied this technique to the model of TNBS-induced rat colitis, to characterize the effects of inflammation on the response of individual CSMC to the excitatory agonists carbachol (CCh), 5-HT, and histamine over the time course of inflammation from onset to overt recovery (as characterized by the absence of inflammation).…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, the loss of esophageal function has been shown to be a direct consequence of inflammatory injury, affecting muscularis propria and causing decreased muscle tone and contraction amplitudes, as well as esophageal shortening [27,28]. In a study which combined intraluminal esophageal ultrasound with esophageal 24-hour pH metry, manometry, and endoscopy, it has been shown that patients with GERD and IEM had decreased esophageal muscle thickness opposed to GERD patients with normal motility [29].…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of colonic CSMC has been previously described [7,20]. Briefly, strips of circular smooth muscle were isolated from the mid-descending colon and placed into 4-2-hydroxyethyl-1-piperazineethanesulfonic acid (HEPES) physiological salt solution (HPSS)-digestion solution.…”
Section: Isolation Of Circular Smooth Muscle Cellsmentioning
confidence: 99%